Application of endovascular embolization of the middle meningeal artery in the treatment of chronic subdural hematomas: A literature review - Yurii O. Kotlyarevskyi; Yuliia G. Serhiienko; Volodymyr O. Piatykop (Ukrainian Neurosurgical Journal)
Introduction. Interest in this research topic arises from the fact that chronic subdural hematoma (CSDH) is currently one of the most common neurosurgical diagnoses in adults. Over the past decade, the incidence of CSDH has more than doubled. Recent studies have significantly enhanced our understanding of the mechanisms underlying the formation of CSDH, linking it to recurrent microbleeds in the subdural space from fragile, newly formed vessels within the hematoma capsule. Most of these vessels originate from the distal branches of the middle meningeal artery (MMA). Accordingly, endovascular embolization of the MMA may help eliminate chronic recurrent bleeding into the subdural space and facilitate hematoma resorption. Objective of the study. To summarize current concepts regarding the pathophysiology of CSDHs and analyze the implementation and use of endovascular embolization of the MMA in contemporary treatment strategies for CSDH based on literature data. Results. A detailed analysis of the literature indicates that a new understanding of the primary pathological process of CSDH has substantiated approaches to diagnosing and treating this pathology as an angiogenic process. Recent research findings demonstrate that endovascular embolization of the MMA in patients with CSDH is a safe and effective method to prevent recurrence or progression of subdural hematomas. Comparing different classes of embolic materials in the treatment of patients with CSDH represents the next step in ongoing research aimed at standardizing the overall treatment protocol for chronic subdural hematoma.